Analisis Kuat Tekan Beton Dengan Penambahan Zat Aditif - Djau, Rahman A.; Bumulo, Nasir; Ma’sum, Ratna Dwi; Ismail, Anjani Eka Putri (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to determine the effect of Addition H.E, Bestmittel, and Tricosal BVS on the compressive strength of characteristic concrete using experimental research methods / quantitative comparisons. Based on the test results on the addition of the three types of additives, it can be concluded that the compressive strength value of concrete obtained from the addition of the Addition H.E additive with a variation of the addition of 0.2% obtained a characteristic concrete compressive strength value of 340.00 kg/cm², and with a variation of the addition of 0.6% 100.09 kg/ cm². The addition of the Besmittel additive with a variation of 0.2% addition obtained a characteristic concrete compressive strength value of 359.60 kg/cm², and with a variation of the addition of 0.6% 31.38 kg/cm², while the addition of the additive Tricosal BVS with a variation of the addition of 0.2% obtained a compressive strength value of concrete characteristics of 322.22 kg/cm², and with a variation of the addition of 0.6% 343.13 kg/cm², while the BVS Tri-cosal additive showed an increase in concrete compressive strength at the addition of 0.6%.